Therapeutic properties of trees and shrubs cultivated in the green spaces of the Algerian Sahara - Souddi, Mohammed; El Zerey-Belaskri , Asma; El Zerey, Wael; Bouallala , M'hammed (Ethnobotany Research and Applications, 2025)
Background: Ethnobotanical studies are essential for understanding cultural diversity, the use of plant resources, drug discovery, and biodiversity conservation efforts. The current research highlights the medicinal properties of trees and shrubs growing in urban green spaces in the Algerian Sahara. Methods: A total of sixty-five (65) articles published in academic journals between 1993 and 2024 were examined to identify the types of diseases treated, the plant parts used and the methods of preparing medical recipes from trees and shrubs growing in Saharan urban green spaces. The data were analyzed using statistical tools and techniques. Results: Sixteen species belonging to 12 families and 15 genera were reported as being used to treat various diseases, grouped into 12 main categories. These include digestive, respiratory, dermatological, cardiovascular, endocrine, urinary, hematological diseases, musculoskeletal disorders and sexual problems. The plant families most commonly used to treat various diseases are Fabaceae (with 3 species), Lythraceae and Tamaricaceae (each with 2 species). Conclusions: The findings provide valuable baseline information for further studies on the bioactive compounds derived from medicinal plants in Saharan urban green spaces, which may be effective in the treatment of various diseases. Keywords: Biodiversity; Green spaces; Medicinal properties; Diseases; Sahara; Algeria